Improving Health Equity Through Team Observed Structured Clinical Encounters with LEP Standardized Patients and Healthcare Interpreter Trainees. - Ramirez-Polo, Laura; Rodriguez, Stephanie A.; Blumenfield, Julie; Horan, Kathleen; Merrigan Robertazzi, Marisa; Short, Jennifer (International Journal of Language, Translation and Intercultural Communication, 2025)
When language barriers exist, patients who do not share a language with their providers are at risk of poorer medical outcomes, adherence, trust, and follow-up care (Sentell et al. 2016; Eslier et al. 2023; Luton et al. 2022; Nadakuditi 2023). These barriers drive the need for Translation and Interpreting programs that prepare students for healthcare settings. This study examines interpreter-mediated communication in midwife consultations within New Jersey, where 12.4% of residents are LEP (New Jersey Department of Community Affairs 2022). An interprofessional simulation was piloted, engaging Translation and Interpreting students alongside Women’s Health/Nurse Midwifery students, providing specialized training in bilingual health communication. Pre- and post-intervention surveys collected data, revealing that the educational intervention effectively boosted interpreting students' confidence, improved their terminology knowledge, and enhanced their understanding of providing equitable, quality care to LEP patients in their native language.